Pengaruh Motivasi dan Pelatihan Kerja terhadap Kinerja Karyawan di Hotel HR Bali - Ida Ayu Nyoman Yuni Devi Antari; Ni Desak Made Santi Diwyarthi; I Wayan Jata (TOBA: Journal of Tourism, Hospitality, and Destination, 2024)
This research aims to determine the influence of motivation and job training on employee performance at HR Bali Hotel. This research was conducted using proportional area random sampling, randomly selected based on the population of employees in each sub-population. Therefore, the sample to be used in this study consists of 100 individuals from HR Bali Hotel. The analysis techniques used include validity testing, reliability esting, classical assumption testing, simple linear regression analysis, the coefficient of determination test, and the t-test. The data analysis technique used is multiple regression analysis with the help of the Statistical Program for Social Science (SPSS). The research design employed is a quantitative design with a survey approach. The population used in this study involves all employees working at HR Bali Hotel, totaling 313 individuals. The sample used in this study is employees working at HR Bali Hotel, totaling 100 individuals. The sampling technique used is proportional random sampling using the Slovin formula. The results of the study show that motivation and job training, both partially and simultaneously, have a positive and significant effect on employee performance at HR Bali Hotel.